Scutellaria baicalensis and its flavonoids in the treatment of digestive system tumors - Zhao, Kangning; Zhang, Jinlong; Zhou, Lin; Sun, Zhen (Frontiers in Pharmacology, 2024)
Scutellaria baicalensis has been used for the treatment of digestive system disorders for thousands of years in China and other regions. Modern research have revealed its therapeutic efforts in digestive system tumors. Thus, to review the updated progress of Scutellaria baicalensis and its main flavonoids in the treatment of digestive system tumors in the past 10 years, this article summarized the therapeutic effect and molecular mechanisms of Scutellaria baicalensis and its 5 flavonoids on tumors in oral cavity, esophagus, stomach, colon, liver, pancreas by inhibiting tumor cell proliferation, inducing autophagy, stimulating immune response, and increasing drug sensitivity. In conclusion, Scutellaria baicalensis and its flavonoids could be applied to treat digestive system tumors with different type of methods.